2020
DOI: 10.1080/21870764.2020.1864899
|View full text |Cite
|
Sign up to set email alerts
|

Flash sintering of hydroxyapatite ceramics

Abstract: The flash sintering process has been regarded as a noble method to densify ceramic materials. The distinctive feature of the flash sintering is the reduced sintering time which is caused by the electric field. In this study, flash sintering of the hydroxyapatite bioceramics was carried out at temperatures of 900-1200°C and electric fields of 500-1200 V/cm. Dense sintered sample was prepared in a short time within 10 seconds. Electric field required for flashing became reduced as the furnace temperature increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…This leads to finer microstructures, higher thermal stability, and subsequently better mechanical properties of CaPO 4 bioceramics. In addition, microwave [301][302][303][304][305][306], spark plasma [69,104,[307][308][309][310][311][312][313][314][315], flash [316,317], and ultrafast high-temperature [318] sintering techniques are alternative methods to the conventional sintering, hot pressing, and hot isostatic pressing. Both alternative methods were found to be time-and energy-efficient densification techniques.…”
Section: Sintering and Firingmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to finer microstructures, higher thermal stability, and subsequently better mechanical properties of CaPO 4 bioceramics. In addition, microwave [301][302][303][304][305][306], spark plasma [69,104,[307][308][309][310][311][312][313][314][315], flash [316,317], and ultrafast high-temperature [318] sintering techniques are alternative methods to the conventional sintering, hot pressing, and hot isostatic pressing. Both alternative methods were found to be time-and energy-efficient densification techniques.…”
Section: Sintering and Firingmentioning
confidence: 99%
“…They can exhibit an optical transmittance of ~66% at a wavelength of 645 nm [425]. The preparation techniques include a hot isostatic pressing [87, 185,187,426], an ambient-pressure sintering [420], a gel casting coupled with a low-temperature sintering [421,424], and a pulse electric current sintering [422], as well as spark plasma [69,[307][308][309][310][311][312][313][314][315] and flash [316,317] sintering techniques. Fully dense, transparent CaPO 4 bioceramics are obtained at temperatures above ~800 • C. Depending on the preparation technique, the transparent bioceramics have a uniform grain size ranging from ~67 nm [87] to ~250 µm [421] and are always pore-free.…”
Section: Possible Transparencymentioning
confidence: 99%
“…Sintering of HA coatings is fundamental because the mechanical performance and the biological behavior of a coating are controlled by processes of particle consolidation and coating structure formation. As shown in [27,28], the main purposes of sintering technology are to save the coating microstructure and phase composition and control coating porosity, grain size, adhesion, and bonding strength. From this viewpoint, the application of Pressureless Sintering technology (in the electric resistance chamber furnaces) in ambient air looks reasonable because of the presence of water vapor in the sintering atmosphere that allows for saving HA Ca 10 (PO 4 ) 6 (OH) 2 phase composition.…”
Section: Coating Sinteringmentioning
confidence: 99%
“…Studies also revealed that sintering in a vacuum was more beneficial than in air. At elevated temperatures, the dehydration of HAp leads to the generation of hydroxyl or hydrogen type defects, leading to an increase in the electric current during FS [ 59 ]. In conventional sintering, a higher temperature initiates the transition of the β phase to the α phase of TCP.…”
Section: Conventional Sinteringmentioning
confidence: 99%